Grey matter changes in cognitively impaired Parkinson's disease patients - Rektorova, Irena; Biundo, Roberta; Marecek, Radek; Weis, Luca; Aarsland, Dag; Antonini, Angelo (PLoS One, 2014)
BACKGROUND: Cortical changes associated with cognitive decline in Parkinson's disease (PD) are not fully explored and require investigations with established diagnostic classification criteria. OBJECTIVE: We used MRI source-based morphometry to evaluate specific differences in grey matter volume patterns across 4 groups of subjects: healthy controls (HC), PD with normal cognition (PD-NC), PD with mild cognitive impairment (MCI-PD) and PD with dementia (PDD). METHODS: We examined 151 consecutive subjects: 25 HC, 75 PD-NC, 29 MCI-PD, and 22 PDD at an Italian and Czech movement disorder centre. Operational diagnostic criteria were applied to classify MCI-PD and PDD. All structural MRI images were processed together in the Czech centre. The spatial independent component analysis was used to assess group differences of local grey matter volume. RESULTS: We identified two independent patterns of grey matter volume deviations: a) Reductions in the hippocampus and temporal lobes; b) Decreases in fronto-parietal regions and increases in the midbrain/cerebellum. Both patterns differentiated PDD from all other groups and correlated with visuospatial deficits and letter verbal fluency, respectively. Only the second pattern additionally differentiated PD-NC from HC. CONCLUSION: Grey matter changes in PDD involve areas associated with Alzheimer-like pathology while fronto-parietal abnormalities are possibly an early marker of PD cognitive decline. These findings are consistent with a non-linear cognitive progression in PD.
Keywords: Neuropsychological Tests; demence; Magnetic Resonance Imaging; Humans; mezencefalon; neuropsychologické testy; lidé středního věku; Mesencephalon; Middle Aged; Cognitive Dysfunction; spánkový lalok; magnetická rezonanční tomografie; mužské pohlaví; Hippocampus; Parkinson Disease; kognitivní dysfunkce; temenní lalok; Dementia; Cerebellum; Temporal Lobe; mozeček; ženské pohlaví; lidé; hipokampus; Parkinsonova nemoc; Aged; senioři; Male; Parietal Lobe; Female